Is a Transdisciplinary Theory of Engagement in Organized Settings Possible? A Concept Analysis of the Literature on Employee Engagement, Consumer Engagement and Patient Engagement - Graffigna, Guendalina (Frontiers in Psychology, 2017)
Organizations are experiencing increased competition, disruptive innovation, and continuous changes in their social and economic context. Furthermore, the decrease of resources (economic and human) in such a demanding context make it imperative for organizations to find new models and strategies to make their service delivery more sustainable at the economic, environmental and psychological levels. In such a complex scenario the concept of engagement of the individuals involved in organized settings (either as service providers or as final receivers) is a promising lever for innovation. However, despite the number of studies on the matter, the debate on engagement is still very fragmented because the corpus of literature addressing the different areas of engagement is divided and diverse in its nature. In this paper, we discuss the results of a conceptual analysis of the literature conducted in order to investigate overlapping features and areas of divergence among three different areas of investigation and application of the engagement phenomenon in organized settings: the domains of employee engagement, consumer engagement, and patient engagement. These are deliberately selected as prototypical of the phenomenon of engagement along the “inside/outside” of organizational settings. The analysis consisted in a qualitative conceptual survey? Of the scholarly literature indexed with the key terms “employee engagement,” “consumer engagement,” and “patient engagement.” We performed a key-word based survey? Of the literature in the Scopus database. A total of 163 articles were selected and analyzed. The analysis cast light on the following areas of conceptual overlap among employee, consumer and patient engagement: (1) engagement is different from empowerment and activation; (2) engagement is a multi-componential psychological experience; (3) engagement is a self-transformative experience; (4) engagement develops within a relational context; (5) engagement is a systemic phenomenon. These findings, although preliminary and in need of further investigation, suggest the feasibility of promoting a transdisciplinary reflection on the phenomenon of engagement in organized settings.